El Excentrico, 1973-11-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
November 5, 1973 [5 de noviembre de 1973]. No volume or issue number. Cover has a photograph of a man injecting drugs to highlight the Eastside Drug Abuse Center Open House